The impact of recent economic crises on income inequality and the risk of poverty in Greece - George Petrakos; Kōnstantinos *ca. 20./21. Jh.* Rontos; Chara Vavoura; Iōannēs S. Baburas (Economies, 2023)
We consider the impact of the two recent economic crises, one that resulted from the great recession of 2007-2009 and one following the COVID-19 pandemic, on income inequality and the risk of poverty in Greece. To this end, we also investigate the key macroeconomic variables affecting the Greek income distribution. We find that alternative measures of inequality and relative poverty have deteriorated during the years of crises, implying that the country's response to economic shocks has been particularly harmful for its more disadvantaged citizens. Regarding the variables affecting the income distribution, we show that income inequality and the risk of poverty increase with growth, implying that the benefits of growth, and burdens of recession, are distributed unequally among members of the Greek society. Moreover, inequality appears to increase with unemployment and decrease with the share of wages and salaries in total income. This finding highlights the importance of labour market regulations and workers' welfare for attaining equality. Finally, we provide evidence that, during pre-election periods, income inequality is reduced, meaning that the political budget cycles, which are characteristic of the Greek economy, generate gains in terms of equality, but these gains are short-lived and mainly benefit the middle bracket of the income distribution.
Keywords: D31; D63; E02; 330; inequality; Gini coefficient; income quintile share ratio; risk of poverty rate; income inequality; economic crises